Entre redes, linhas, tarafas e puçás : o cotidiano do pescador barra-coqueirense em meio ao contexto urbano e a dimensão socioambiental - Souza, Nara Vieira de (2019)
The occupation of the coastal strip has been emphasized in several surveys worldwide, becoming a global phenomenon, being seen by different factors and by the appearance of new senses for practices and uses of natural resources in this space. In Brazil, and considering the state of Sergipe, highlighting the municipality of Barra dos Coqueiros, locus of this study, the scenario for the coastal strip has not been different, and, with greater intensity from the end of 2006, after construction of the bridge João Alves, known as the Aracaju-Barra bridge, which triggered interference in the natural resources and in the daily life of traditional communities, as in the case of fishermen, subject of this research. New meanings and practices in the coastal space, at the global level, stand out for the vectors that signal interests for modernization, for the increase of riches (real estate speculation, summer, tourist activity, villas on the seafront), for the interests in the use of space for exploration offshore oil, and, more recently, the interests also tend to set up large enterprises with high investments (wind farms, thermoelectric plants and other industries). Facts that cause disputes and major modifications with the population and occupational densification, changing the socioenvironmental dynamics and the man-nature relations of traditional communities, without emancipatory transformations. In the case of Barra dos Coqueiros-SE, the interferences occurred affected urban and rural areas of the municipality, either in structural aspects, natural resources and economic activities peculiar to the municipality, such as fishing, which is an activity with comings and goings, an everyday life of fishermen with nature, whether in estuarine, coastal or coastal waters, with daily rhythms as producers of knowledge in the relation between man and nature, and which must necessarily be involved in all socioenvironmental planning. In this context, the research analyzes the daily life of the Barra- Coqueirenses fishermen, their transformations, changes in the use of natural resources, due to the projects that emerged in the period from 2007 to 2017, from a socio-environmental perspective as a parameter of local development. Methodologically, the research used the dialectical method, with Discourse Analysis (AD) technique, instruments such as semistructured interviews and recorders for ethnographic stage with fishermen and representatives of the fishing demands of the municipality, in a process of collecting data described historically and dialogically analyze the daily life of fishermen. For the treatment of the data were used the software's, DSCsoft and Iramutec, that allowed groupings by central ideals and by similarities, resulting in figures and pictures from the narratives inserted in said programs. As a contribution of the research, a socioenvironmental circuit of local transformation and a socioenvironmental agenda was constructed, consisting of elements for a management in the conception of local development for the municipality, given the established development model, it does not present aspects of an integrated local development